Corrections to “Padial et al. (2014) Molecular systematics of terraranas (Anura: Brachycephaloidea) with an assessment of the effects of alignment and optimality criteria” - Padial, José M.; Grant, Taran; Frost, Darrel R. (Zootaxa, 2014)
Padial et al. (2014) applied the name Pristimantinae Ohler & Dubois, 2012 to a taxon including the genera Ceuthomantis, Dischidodactylus, Pristimantis, and Yunganastes. However, Ceuthomantidae Heinicke, Duellman, Trueb, Means, MacCulloch & Hedges, 2009, type genus Ceuthomantis Heinicke, Duellman, Trueb, Means, MacCulloch & Hedges, 2009, has priority over Pristimantinae Ohler & Dubois, 2012, a fact that we overlooked and correct herein. Ceuthomantinae is thus the correct subfamily name for the taxon including Ceuthomantis, Dischidodactylus, Pristimantis, and Yunganastes, and Pristimantinae Ohler & Dubois, 2012 is its junior synonym. We provide an amended Figure 22 (page 50) reflecting the current classification of Brachycephaloidea as now listed in Frost (2014) and provide the pertinent correction to page 125 of Appendix 2, which should read as follows: